Kurikulum Merdeka Berbasis Pembelajaran Berdiferensiasi Perspektif Pendidikan Islam - Ahmad Muktamar; Rahmawati; Abdul Jalil; Muhammad Tang; Irwan; Jaja Miharja (PT. Banjarese Pacific Indonesia, 2023)
This research examines an independent curriculum based on differentiated learning with an Islamic education perspective. An independent curriculum based on differentiated learning can be interpreted as the implementation of Islamic values ​​which views each individual as unique and entitled to education that suits his or her capacity. The method used in this research is a descriptive qualitative approach, with data collection carried out through a literature review. The focus of the research is to explore various types of literature, such as books, notes and previous research reports which discuss the implications of the independent learning policy on the development of assessments in the independent curriculum with an Islamic religious education approach. The secondary sources used include national journal articles, books, and other relevant information to investigate assessment development models in the independent curriculum with an Islamic religious education perspective. Research findings show that assessment in the independent learning curriculum has a crucial role in ensuring the smooth learning process.